a 1 + b 1 If a , b are non-zeros satisfy a b ( a + b ) = a 2 − a b + b 2 , find the sum of the maximum and the minimum value of the expression above
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Harsh Shrivastava What abt minimum???
Consider a + b = η & a b = ω .
Using few basic algebraic identities one can easily arrange above given relation as
ω = η 2 / ( 3 + η ) .
Therefore the above
1 / a + 1 / b = 1 + 3 / η
Also we have boundary conditions on η , through :
η = a / b + b / a − 1
Therefore boundries for η are 1 & -3 .
Putting those we get answer as 4
Problem Loading...
Note Loading...
Set Loading...
Rearrange the given conditions to get a b ( a + b + 1 ) = a 2 + b 2
Using cauchy-schwarz inequality, a 2 + b 2 = a b ( a + b + 1 ) ≥ 2 a 2 + b 2 + 2 a b
⟹ 2 a b ( a + b ) ≥ a 2 + b 2
Again by Cauchy Schwartz inequality 2 a b ( a + b ) ≥ a 2 + b 2 ≥ 2 ( a + b ) 2
⟹ 4 ≥ a b a + b
Equality holds when a = b = 2 1